The grand Lusin‐area characterization of Hajłasz‐Sobolev spaces and Triebel‐Lizorkin spaces1. Issue 7 (11th April 2012) - Jiang, Xiaojuan; Yang, Dachun; Yuan, Wen; Haroske, Dorothee D.; Schmeißer, Hans‐Jürgen
Abstract In this paper, the authors establish the grand Lusin‐area characterization of the Hajłasz‐Sobolev spaces and, more generally, the Triebel‐Lizorkin spaces on both Euclidean spaces and RD‐spaces, namely, metric spaces enjoying both doubling and reverse doubling properties.